The Effect of Fingerprint Attendance System Implementation on Civil Servants' Work Discipline at the Makassar City Manpower Office - Nurul Insani; Nurinaya; Irwan Abdullah (GoodWill, 2026)
This study investigates the effect of fingerprint attendance system implementation on the work discipline of civil servants at the Makassar City Manpower Office. Although biometric attendance systems have been widely adopted in public sector organizations, empirical findings regarding their effectiveness remain inconsistent, particularly within local government institutions. This study employs a quantitative explanatory approach using a saturated sampling technique involving 57 civil servants. Data were collected through structured questionnaires, observations, and documentation, and analyzed using simple linear regression with SPSS version 27. The results reveal that the implementation of the fingerprint attendance system has a positive and significant effect on employee work discipline, as indicated by a t-value of 6.767, which exceeds the critical value of 1.673, with a significance level of 0.000. The regression coefficient shows that improvements in the implementation of biometric attendance systems are associated with increased employee discipline, particularly in terms of punctuality, compliance with attendance schedules, and adherence to organizational regulations. The coefficient of determination (R²) indicates that 45.4% of the variation in work discipline is explained by the fingerprint attendance system. These findings highlight the role of digital attendance systems as effective managerial control mechanisms in enhancing accountability and discipline within public sector organizations. The study contributes to human resource management literature by providing empirical evidence from a local government context and offers practical insights for policymakers to optimize attendance systems and strengthen organizational discipline.